Optimal bioenergy power generation for climate change mitigation with or without carbon sequestration - Dominic Woolf (Nature Portfolio, 2016)
Prior mitigation assessments of atmospheric CO2 removal rely on bioenergy carbon capture and storage (BECCS), excluding bioenergy-biochar systems (BEBCS). Here, Woolf et al. find that BEBCS offers an alternative cost-effective solution, and may allow earlier CO2removal at a lower carbon price.